Evaluation of the antifungal efficacy of ethyl acetate extracts of Alternaria citri against the white-rot wood decaying fungi Schizophyllum commune and Ganoderma applanatum in some coastal regions of Syria (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Biological Sciences Series, 2026)
This study evaluated the antifungal activity of ethyl acetate extracts obtained from the fungus Alternaria citri against two basidiomycete fungi, Schizophyllum commune and Ganoderma applanatum, which are responsible for white rot disease in wood. Extracts derived separately from both the culture filtrate and the fungal biomass of the imperfect fungus were used in the assays.The results demonstrated that the tested extracts exhibited inhibitory activity against the two studied basidiomycete fungi. This activity varied according to the kind and concentration of the extract, as well as the fungal species treated. At a concentration of 50 mg/mL, both the culture filtrate extract and the biomass extract of the tested fungus caused complete inhibition (100%) of mycelial growth of the two basidiomycete fungi.Furthermore, the biomass extract showed higher inhibitory efficacy than the culture filtrate extract at concentrations of 30 mg/mL and 40 mg/mL against S. commune, with inhibition percentages of 64.70% and 23.52%, respectively. In contrast, the inhibition percentages against G. applanatum at the same concentrations were 35.29% and 17.64%, respectively. At a concentration of 10 mg/mL, neither the culture filtrate extract nor the biomass extract of A. citri exhibited any inhibitory activity against the two basidiomycete fungi under study.These results highlight the potential use of Alternaria citri extracts as a promising biological source for controlling wood-decay fungi under laboratory conditions.
Keywords: Antifungal Activity, Organic Extracts, White Rot Fungi, Alternaria citri, Ethyl Acetate.